Fiscal policy reaction to the cycle in the OECD: Pro- or counter-cyclical? - Balázs Égert (Center for Economic Studies and ifo Institute (CESifo), 2012)
This paper analyses the reaction of fiscal policy to the cycle in OECD countries. The results suggest that while overall government balances were counter-cyclical in the past and more so in economic downturns than in upswings, discretionary fiscal policy was neutral on average. However, discretionary fiscal policy appears to react to the cycle in a non-linear fashion: fiscal policy in countries with high public debt and high government deficits tends to be pro-cyclical, while countries that have low public debt and that have surpluses are more likely to conduct a counter-cyclical fiscal policy. The paper also finds that asset prices have a significant impact on government balances.
Keywords: E32; E62; H21; H30; H60; C33; 330; fiscal policy; pro-cyclicality; counter-cyclicality; OECD countries